Complexos de Pd(II) e Pt(II) contendo tiossemicarbazonas derivadas do tiofeno: síntese, caracterização, investigação da citotoxicidade e modo de ação - Oliveira, Gabriela Porto de (Universidade Federal de São Carlos, 2022)
In this work, ten ligands and four palladium and two platinum complexes containing thiosemicarbazones derived from thiophene were synthesized in order to evaluate their cytotoxic profile against tumor cells. The compounds were characterized by molar conductivity, Nuclear Magnetic Resonance (31P{1H}, 1H and 13C{1H} NMR, COSY, HMBC, and HSQC), Infrared (IR) Absorption Spectroscopy, Ultraviolet-Visible Absorption Spectroscopy, Elemental analysis, ESI/MS Mass Spectrometry, and Single Crystal X-ray Diffraction (XRD). From the set of techniques, it was possible to verify that the ligands coordinated in an anionic bidentate form, with the exception of the PtT complex, which coordinated in a neutral form, via nitrogen and sulfur atoms of the thiosemicarbazone and the other sites are occupied by a chloride ligand and a triphenylphosphine. The compounds were subjected to stability tests in DMSO, which suggested the permanence of the chloride ligand in the coordination sphere. Afterwards its cytotoxicity was evaluated by the MTT method against the tumor cell lines DU-145 (prostate), A549 (lung), MDA-MB-231 (breast), A2780 Cis (ovary) and non-tumor cell line MRC5 (lung). The ligands were inactive in all cell lines tested, while the complexes were more promising concerning the A549 and A2780 Cis tumor lines. The most cytotoxic compound PdT showed cytostatic behavior against the A549 tumor lineage, while the PdCH3 compound exhibited antimetastatic and cytotoxic behavior against the A2780 Cis cell line. To explore a possible biological target, DNA interaction assays were performed. These data indicate that the complexes interacted with DNA only at high concentrations (100 uM). Moreover, they suggest that the interaction pathway is electrostatic and/or via groove binding with DNA. Additionally, they could not inhibit the action of topoisomerase IIα and IIβ enzymes. However, the platinum complexes inhibited topoisomerase Iβ at all concentrations evaluated (0.1-100 μM). The most promising compound, PdCH3, provided the accumulation of cells in the sub-G1 phase of the cell cycle, which may indicate induction of apoptosis. Furthermore, this complex inhibited wound closure in Wound Healing assays and significantly altered cell morphology. Such data represent an effective ability to affect the cell viability of cancer cells. These results indicate that the synthesized palladium compounds have an encouraging biological activity.
Pd(II) and Pt(II) complexes containing thiosemicarbazones derived from thiophene: synthesis, characterization, investigation of cytotoxicity and mode of action
Keywords: DNA; Citotoxicidade; Enzimas Topoisomerases; Tiossemicarbazonas; Complexos paládio; Complexos platina; Cytotoxicity; Topoisomerase enzymes; Thiosemicarbazones; Palladium complexes; Platinum complexes; CIENCIAS EXATAS E DA TERRA::QUIMICA